DruBot: Robotic prototype for authentication and comparison of facial proportions for assistance control and impersonation detection in evaluations - Yallico Arias, Tereza (2019)
The work ‘DruBot: Robotic prototype for authentication and comparison of facial proportions for assistance control and impersonation detection in evaluations’ describes the development of the robotic prototype called DruBot that seeks to recognize the faces of the persons who join to a classroom specific, a private area or an examination, comparing them with a database for each case (to distinguish them from the characteristics extracted from the photo of the university identification and the frames obtained of the video of welcome of every student) and to determine if the image of the person which camera is capturing has or hasn’t access to the area, issuing a different sign if his or her access is allowed or not. We apply technologies of artificial vision (Haar cascade for the detection of faces in the whole image captured by camera in real time and Face Landmarks to find the key points of human detected face, to calculate his proportions with Euclidean distances and to compare for the recognition of every person in specific) and serial communication with electronic devices so that the presents notice when there is an intruder or when the student has been recognized well and register his or her assistance.